Smart city initiatives: A comparative study of American and Chinese cities - Hu, Qian; Zheng, Yueping (Journal of urban affairs, 2021)
Taking a comparative approach, this study conducted text-mining and content analysis of smart city initiatives to evaluate the status and progress of smart city development in China and the United States. Despite sharing similarities in developing and applying technology to improve  public services and promote economies, these cities have taken different approaches to building smart cities. The American cities adopted a participatory governance structure whereas the Chinese cities demonstrated a hierarchical model that highlighted a proactive role of government and lacked systematic mechanisms for stakeholder engagement. The American smart city initiatives emphasized the improvement of public services to attract businesses and the use of a collaborative approach to building digital infrastructure. With a higher level of policy support and funding support from the central government, local Chinese governments have assumed a leading role in nurturing and developing the smart technology industry, protecting the environment, and building intelligent infrastructures.